1994
DOI: 10.1111/j.1365-3032.1994.tb01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive behaviour of the South American fruit fly Anastrepha fraterculus (Diptera: Tephritidae): laboratory and field studies

Abstract: Abstract. The mate choice, courtship and oviposition behaviour of laboratory‐reared and field‐collected Anastrepha fraterculus (Wied.) were compared. In laboratory cultures in Southampton the duration of male calling activity in small leks increased gradually from 1‐2h at 5 days old to up to 7 h at 10 days. This finding correlates with previous reports on the time at which male salivary glands, which are believed to produce sex pheromone, are fully developed. Wild flies which emerged from infested fruits in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
1
18
2
1
Order By: Relevance
“…There were also differences regarding maximum longevity, and this was greater for the adults in the present study. However, Lima et al (1994) reported mean longevity in adult A. fraterculus greater than that obtained here. A. obliqua longevity, from mango, was similar to that obtained by Carvalho et al (1998) although in the present study some females presented higher values.…”
Section: Discussioncontrasting
confidence: 54%
“…There were also differences regarding maximum longevity, and this was greater for the adults in the present study. However, Lima et al (1994) reported mean longevity in adult A. fraterculus greater than that obtained here. A. obliqua longevity, from mango, was similar to that obtained by Carvalho et al (1998) although in the present study some females presented higher values.…”
Section: Discussioncontrasting
confidence: 54%
“…These results also have interesting implications when compared with those obtained for A. fraterculus complex , De Lima et al 1994, which was treated as a single species until results of crossing experiments and discovery of substantial differences in genetical criteria led to the description of at least two seperate species (Selivon et al 1999). Informal observations (F. Henning, unpublished) suggest differences in mating times between these recently described A. fraterculus species.…”
mentioning
confidence: 87%
“…the first probing behaviour was observed. The results of these observations led us to believe that female flies were attracted to salivary glands of calling males only when they reached sexual maturation, which is on average 16 days old 15 .…”
Section: Behavioural Activitymentioning
confidence: 98%